Os desafios para a integração curricular no ensino médio em uma escola pública de educação básica - Silva, Luís Eduardo da (2017)
This research aimed to improve the understanding of some aspects of curricular restructuring policies of High School, considered here as a general theme. The research was developed in the context of a public school of basic education of the state network in Rio Grande do Sul, where a process of implementation of an educational policy focused on the curricular restructuring of High School took place in the period from 2011 to 2016. Among the characteristics of this policy we highlight the insertion of a new curricular component, called Integrated Seminar. The objective was to provide a space for curricular integration to be carried out under the coordination of a teacher. Another important aspect of the policy was the organization of the disciplines in areas of knowledge, from the perspective of curricular integration, a characteristic that remains to this day. Thus we arrive at the specific theme of the research, that is, curricular integration in High School. One of the main challenges in the recontextualization process of this educational policy, at least in the case of the institution researched, was the difficulty of performing the curricular integration, which was experienced in the daily school life by the researcher himself in the exercise of his work as a teacher in High School. This challenge instigated the realization of this research, whose objective was to signal possibilities and limitations for the organization and development of teaching work in High School, aiming to effect curricular integration. The focus of this research is the organization and development of teaching work in the perspective of curricular integration in High School. We developed a qualitative research by conducting five focus groups with regent teachers and three individual interviews with each member of the management team, in the period of November and December 2016. The analysis of the collected data pointed to the planning and execution of the actions of the teaching work predominantly in an individual and isolated way, for the organization of the school work that sought to promote the curricular integration between the disciplines. We identified some factors that contributed to this situation, among which we highlight the fact that the school did not provide the conditions to promote times and spaces so that teachers could dialogue and carry out an effective curricular integration among the disciplines. We also observed that the process of curricular restructuring of Secondary School generated a demand for continuous training for teachers and management team, especially on the integrated seminar. In order to overcome the identified challenges, in order to achieve an integrated curriculum, we point out some possibilities, among which are: (1) to promote a process of continuous formation about the planning and accomplishment of school and teaching actions in the perspective of curricular integration; (2) hold weekly group meetings per area of knowledge at school included in the teachers' workload. From the limits and possibilities identified, we elaborated a proposal of organization of the teaching work for the researched school, aiming the development of an integrated curriculum in High School. We believe that the main contribution of this research was to promote spaces where teachers who work in High School in the school investigated could think about the process of curriculum management aimed at curricular integration.